Health from the perspective of monotheistic school - Mohammad Reza Razaghi (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here. From the perspective of monotheistic school, health will be meaningful with a comprehensive knowledge of the origin of the universe and God's attention to all the creatures. As reflected in the narratives, the health as one of the greatest divine blessings along with security are more neglected and ingratitude. Health is not limited only to physical, social and psychological aspects and at present, the fourth dimension added to the health is the spiritual health.  Definitely more dimensions will be inserted to it in the future... . For downloading the full-text of this article please click here.